Plastic Food Packaging: Perceptions and Attitudes of Portuguese Consumers about Environmental Impact and Recycling - Macena, Morgana (2022)
The use of plastics for packaging has some advantages, since they are flexible and inexpensive. However, most plastics are of single use, which, combined with low recycling or reuse ratios, contributes substantially to environmental pollution. This work is part of a project studying the habits of Portuguese citizens concerning plastic food packaging and focuses on aspects related to sustainability. The survey was carried out via an online questionnaire about sustainability, recycling, and knowledge of the effects of plastic materials or their residues on the environment. The results were obtained based on a statistical analysis of the data. The participants tend to think about the negative impact of plastic packages on the environment; 39% sometimes do not buy plastic; and 30% try to look for alternatives. A substantial fraction, 81%, support the avoidance of plastic utensils and reduction in the use of plastic bags. Most participants have a good knowledge of recycling and strongly agree with the use of recycled materials, and 87% of respondents practice separation of different types of waste for recycling. Changing plastic consumption habits has not been an easy task. Nevertheless, it is expected that society will increasingly move toward sustainable habits, questioning its actions and considering their impact on the environment.